Social support and inmate rule violations: A multilevel analysis - Jiang, Shanhe (American journal of criminal justice, 2005)
Social support theory is important in explaining inmate behavior within prison but has been largely ignored in the research. Using multilevel analysis, the study examined the effect of social support on inmate misconduct measured by disciplinary infractions in the 1997 Survey of Inmates of State Correctional Facilities in the United Slates. Findings indicate that several social support variables at both the inmate level and prison level affect inmate rule violations per month.